A terminologization problem of German philosophy in the late 18th and early 19th centuries: a Soviet version - Panafidina, Oksana (Actual Problems of Mind, 2017)
This paper presents a genesis of the term «German classical philosophy» and clariﬁes its meaning within the framework of Soviet investigations of German pre-Marxist philosophy. The author makes a point that this term has an ideological background and lacks scientiﬁc legitimacy beyond the Marxist philosophy.